2021
DOI: 10.1002/brb3.2410
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in brain parenchyma due to mild traumatic brain injury during the first year after injury

Abstract: Chronic gray matter (GM) atrophy is a known consequence of moderate and severe traumatic brain injuries but has not been consistently shown in mild traumatic brain injury (mTBI). The aim of this study was to investigate the longitudinal effect of uncomplicated mTBI on the brain's GM and white matter (WM) from 6 weeks to 12 months after injury. Voxel-based-morphometry (VBM) was computed with the T1-weighted images of 48 uncomplicated mTBI patients and 37 orthopedic controls. Over the period from 6 weeks to 12 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…7 Thus, it is possible that prospective designs may be more sensitive to smaller differences in cortical thinning than cross-sectional designs due to the decreased variance associated with repeat visits. 7,39 Both current and previous 7 prospective pmTBI studies also independently replicated findings of reduced cortical thickness in the right middle frontal gyrus. The prefrontal cortex is commonly affected by TBI pathology across all levels of severity and tended to exhibit the largest effect sizes in the current sample (eFigure 1, links.lww.com/WNL/C525).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…7 Thus, it is possible that prospective designs may be more sensitive to smaller differences in cortical thinning than cross-sectional designs due to the decreased variance associated with repeat visits. 7,39 Both current and previous 7 prospective pmTBI studies also independently replicated findings of reduced cortical thickness in the right middle frontal gyrus. The prefrontal cortex is commonly affected by TBI pathology across all levels of severity and tended to exhibit the largest effect sizes in the current sample (eFigure 1, links.lww.com/WNL/C525).…”
Section: Discussionsupporting
confidence: 72%
“…In contrast, research on atrophy and/or neuropil loss following adult mTBI is more controversial, with mixed results across multiple adult studies. [37][38][39][40] Similarly, previous crosssectional studies in pmTBI have reported no differences in GM volume at 3 months post-pmTBI (N = 26) relative to sibling controls 41 and at 6 months postinjury (age 8-15; N = 219) relative to orthopedically injured controls. 42 Other crosssectional studies have reported increased cortical thickness in the left parietal cortex for patients with pmTBI (age 8 to 16; N = 136) relative to orthopedically injured controls.…”
Section: Discussionmentioning
confidence: 60%
“…Previous studies in this porcine model of TBI, as well as post-mortem human TBI studies, have detailed the presence of diffuse axonal injury, suggesting that white matter pathology is the predominant pathology of diffuse brain injury [5][6][7][8][9][10][11]. Yet recent neuroimaging studies suggest that gray matter atrophy occurs at acute and chronic timepoints after mild TBI in humans [12][13][14].…”
Section: Introductionmentioning
confidence: 84%
“…The ROL, as an essential brain region of the CON, is mainly involved in task initiation, monitoring and maintenance processes and has a role in complex functions, mainly movement, autonomy, sensation, and emotional and cognitive processing [ 33 , 34 ]. A meta-analysis of voxel-based morphometric (VBM) studies reported that migraine patients showed grey matter abnormalities in the left insula and the bilateral ROL [ 33 ] [ 35 ]. Another study based on resting-state BOLD fMRI showed that patients with acute mTBI had less-effective connections from the left insula to the right Rol than healthy controls [ 36 ].…”
Section: Discussionmentioning
confidence: 99%